The solid surprise: laparoscopic discovery of an ovarian fibroma – a case report - N., Sunanda; Karabhantanal, Laxmirani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Ovarian fibromas are uncommon benign sex cord–stromal tumours arising from the ovarian cortex. Although they predominantly occur in peri- and postmenopausal women, they may also present in younger patients. Their solid nature and occasional association with ascites or elevated tumour markers can mimic ovarian malignancy, making preoperative diagnosis challenging. Herein, this case reports the case of a 35-year-old multiparous, tubectomised woman who presented with abdominal pain, distension, and vomiting. Clinical examination suggested a subserosal uterine fibroid. Ultrasonography revealed a solid left ovarian mass measuring 10×5 cm with preserved vascularity and no features of torsion. Serum CA-125 levels were within normal limits. Due to diagnostic uncertainty, diagnostic laparoscopy was performed, which revealed a solid ovarian mass arising from the left ovary. Left salpingo-oophorectomy was undertaken. Histopathological examination confirmed the diagnosis of ovarian fibroma. The postoperative course was uneventful. Ovarian fibroma should be considered in the differential diagnosis of solid adnexal masses, even in younger, premenopausal women. Preoperative distinction from malignant ovarian tumours remains difficult using clinical and ultrasonographic features alone. Surgical excision remains both diagnostic and therapeutic, with laparoscopy offering a safe and effective approach in carefully selected cases.